Exploring End User Preferences for Location Obfuscation, Location-Based Services, and the Value of Location - Brush, A.J.; Krumm, John; Scott, James (Proceedings of UbiComp 2010, 2010)
Long-term personal GPS data is useful for many UbiComp services such as traffic monitoring and environmental impact assessment. However, inference attacks on such traces can reveal private information including home addresses and schedules. We asked 32 participants from 12 households to collect 2 months of GPS data, and showed it to them in visualizations. We explored if they understood how their individual privacy concerns mapped onto 5 location obfuscation schemes (which they largely did), which obfuscation schemes they were most comfortable with (Mixing, Deleting data near home, and Randomizing), how they monetarily valued their location data, and if they consented to share their data publicly. 21/32 gave consent to publish their data, though most households’ members shared at different levels, which indicates a lack of awareness of privacy interrelationships. Grounded in real decisions about real data, our findings highlight the potential for end-user involvement in obfuscation of their own location data.